Aging voices and speech intelligibility: Implications for communication by older talkers - Goy, Huiwen; Pichora-Fuller, M. Kathleen; van Lieshout, Pascal (Canadian Acoustics, 2014)
There are various changes in the voice production system during the course of normal aging. While some older adults have voices that are indistinguishable from those of younger adults, other older adults have perceptibly poorer voices that are characterized by irregularities in fundamental frequency and intensity. Previous studies have demonstrated that listeners perform worse on speech-in-noise tests when speech stimuli are distorted by temporal jittering. In this study, we tested whether natural jitter in the voices of older talkers affected the intelligibility of their speech when it was presented in noise. We selected three older female talkers from a larger pool of older female adults based on several voice acoustic measures, including jitter and harmonics-to-noise ratio; one talker had a relatively poor voice, one talker had an average voice and one talker had a good voice. These talkers recorded stimuli from the NU Auditory Test No. 6, which were then presented to young adult listeners in +1 dB SNR multi-talker babble noise. Surprising, the results showed that the talker with the average voice was the least intelligible of the three older talkers, while the talker with the poorest voice was as intelligible as the talker with the best voice. This pattern of results was reproduced after equating target word intensities across all talkers. Preliminary acoustic analyses showed that the three talkers produced vowels of similar duration and intensity but that the talker with the poorest voice had the slowest speech rate and the longest consonant durations. These findings suggest that older adults with poorer voices may alter their speech behaviour to maintain communication effectiveness despite natural declines in voice quality.